2000
DOI: 10.1093/occmed/50.2.103
|View full text |Cite
|
Sign up to set email alerts
|

Association between Bronchial Hyper-reactivity and Exposure to Silicon Carbide

Abstract: A clinical study of 191 workers in the silicon carbide production industry was carried out in order to determine the prevalence of respiratory symptoms (wheezing, dyspnoea and breathlessness after exercise). Such symptoms occurred in 50 (26.1%) subjects, of whom 24 accepted testing for bronchial reactivity. Of these 24, 19 (79.2%) were positive. These findings suggest that exposure to SiC may be associated with bronchial hyper-reactivity. Positive results were more frequent in women than in men, while differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 15 publications
1
11
0
Order By: Relevance
“…The prevalence, nevertheless, exceeded the prevalence of both "cough without a cold" and "cough for more than 3 months" in our study. Petran et al (2000) in their study of 191 employees in an SiC producing factory found that 26% of the employees had respiratory symptoms. It was stated that the overall occupational exposure was extremely high, making comparison diYcult.…”
Section: Association Between Respiratory Symptoms and Exposurementioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence, nevertheless, exceeded the prevalence of both "cough without a cold" and "cough for more than 3 months" in our study. Petran et al (2000) in their study of 191 employees in an SiC producing factory found that 26% of the employees had respiratory symptoms. It was stated that the overall occupational exposure was extremely high, making comparison diYcult.…”
Section: Association Between Respiratory Symptoms and Exposurementioning
confidence: 99%
“…An increased prevalence of respiratory symptoms, such as "bronchitis symptoms", dyspnoea, wheeze, cough and phlegm, has been reported in workers in the smelting industry compared with the general population or an internal control group in cross-sectional studies (Taddei et al 1979;Langård 1980;Petran et al 2000). The number of participants in each of these studies was less than 200.…”
Section: Introductionmentioning
confidence: 99%
“…Also, an increased mortality from non-malignant respiratory diseases among workers in SiC-producing plants has been shown 6–8. However, in two studies, the findings regarding lung function and respiratory symptoms, were not confirmed 5 9…”
Section: Introductionmentioning
confidence: 89%
“…However, in two of the studies the association between exposure and impaired lung function was only significant in smokers 2 4. Moreover, an increased prevalence of respiratory symptoms among exposed SiC workers has been observed 1 5. Also, an increased mortality from non-malignant respiratory diseases among workers in SiC-producing plants has been shown 6–8.…”
Section: Introductionmentioning
confidence: 95%
“…There is also substantial literature on the association between chronic environmental exposures (4, 5) and obstructive airway diseases (OADs). Occupational exposures, such as to floor sealant, spray paint, metal coat remover, chlorine, sulphur dioxide, ammonia, isocyanates, Western red cedar ( Thuja plicata ), dusts, and fire/smoke, have been associated with increased risks of asthma and bronchial hyperreactivity (69). Dose-response relationships for asthma (allergic-immunologically mediated or irritant) have been well documented (68, 10), although there is insufficient understanding of the timing of disease onset relative to the timing of the triggering exposure (8, 1013).…”
mentioning
confidence: 99%